Einventory of Land Ownership Based on Drone Images in Free Space Transmission Line 150 Kv High Voltage Airlines Kandangan – Incomer Tower T.01 – T.11 Inventarisasi Kepemilikan Tanah Berbasis Citra Drone Di Ruang Bebas Jalur Transmisi Saluran Udara Tegangan Tinggi 150 KV Kandangan - Incomer Tower T.01 - T.11 - Abdul Halid Ary; Mufidah Asy'ari; Suyanto Suyanto (Jurnal Sylva Scienteae, 2025)
ABSTRACT. Forest area is one of the uncertainties that hinders the effectiveness of forest governance. This uncertainty triggers land tenure conflicts with various parties. Forest land tenure issues are related to the implementation of development programs in the electricity sector. Expansion of SUTT network transmission across land, buildings and residents' crops so residents are given compensation and compensation. This study aims to analysis data on land ownership under the transmission line of SUTT 150 kV Kandangan – Incomer from T.01 - T.11. This study used an inventory method using drone imagery in the Kandangan and Padang Batung Districts. The results of study regarding the inventory of drone image-based land ownership in free space of SUTT 150 kV Kandangan - incomer from tower t.01 - t.11 totaled 113 people including 1 PLN land and 1 government land. Land legality status in the form of SPPT totaled 91 people with 82%, SHM totaled 19 people with 17% and grant letters 1 person with 1%. There are 5 buildings, 2 permanent buildings (P), 1 semi-permanent building (SP) and 2 non-permanent buildings (NP). The largest land ownership boundary area T.09 – T.10, that is 2,030.26 m2, The smallest land ownership boundary area T.07 – T.08, that is 12.37 m2. There are 121 function areas consisting of 10 residential areas (KPPm), 87 wetland agriculture (PLB) and 24 dry land agriculture (PLK). The results of this study are useful for PT PLN (Persero) as a provider of compensation funds so that these funds are received by the residents concerned.ABSTRAK. Areal kawasan hutan adalah salah satu ketidakpastian yang menghambat efektifitas tata kelola hutan. Ketidakpastian ini memicu konflik tenurial lahan dengan berbagai pihak. Persoalan tenurial lahan hutan berkaitan dengan pelaksanaan program pembangunan di bidang kelistrikan. Perluasan transmisi jaringan SUTT melintasi tanah, bangunan dan tanaman warga sehingga untuk mempercepat pembebasan lahan, warga diberikan ganti rugi dan kompensasi. Penelitian ini bertujuan untuk menganalisis data kepemilikan tanah yang berada di bawah jalur transmisi SUTT 150 kV Kandangan – Incomer dari T.01 - T.11. Penelitian ini menggunakan metode inventarisasi menggunakan citra drone pada wilayah Kecamatan Kandangan dan Padang Batung. Hasil penelitian mengenai inventarisasi kepemilikan tanah berbasis citra drone di ruang bebas jalur transmisi SUTT 150 kV kandangan – incomer dari tower t.01 – t.11 berjumlah 113 orang termasuk 1 tanah PLN dan 1 tanah pemerintah. Status legalitas tanah berupa SPPT berjumlah 91 orang dengan persentase 82%, SHM berjumlah 19 orang dengan persentase 17% dan surat hibah 1 orang dengan persentase 1%. Terdapat 5 bangunan yaitu 2 bangunan permanen (P), 1 bangunan semi permanen (SP) dan 2 bangunan non permanen (NP). Luas batas kepemilikan tanah terbesar terdapat pada T.09 – T.10 yaitu 2.030,26 m2 sedangkan luas batas kepemilikan tanah terkecil terdapat pada T.07 – T.08 yaitu 12,37 m2. Fungsi kawasan berjumlah 121 fungsi terdiri dari 10 kawasan peruntukkan permukiman (KPPm), 87 pertanian lahan basah (PLB) dan 24 pertanian lahan kering (PLK). Hasil dari penelitian ini berguna untuk PT.PLN (Persero) sebagai pemberi dana kompensasi agar dana tersebut diterima oleh warga yang bersangkutan.